Creating Change in the Workplace: The Role of Leadership in Changing Attitudes and Behaviors - Hajrawati Hajrawati (Institute of Information Technology and Social Science (IITSS), 2020)
Leadership plays a strategic role in driving workplace change through its influence on employee attitudes and behaviors. This study screened and analyzed 184 articles, then selected seven that met the inclusion and exclusion criteria for in-depth review. The review results indicate that effective leadership not only manages the structural aspects of change but also fosters change readiness, increases engagement, and motivates proactive employee behavior. Key interventions include clear and consistent communication, psychological support during transitions, empowered decision-making, and role-modeling by leaders. These factors have been shown to reduce resistance, strengthen trust, and accelerate the adoption of new practices. Furthermore, transformational and adaptive leadership styles have the most consistent impact on successful change implementation in dynamic and uncertain business contexts. The findings underscore the importance of people-focused leadership, with practical implications for organizations designing holistic and sustainable change strategies, while also opening up opportunities for further research related to context, culture, and success metrics.